2010
DOI: 10.1152/ajprenal.00295.2009
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 37 is localized in renal epithelia and responds to changes in dietary salt intake

Abstract: Stoessel A, Himmerkus N, Bleich M, Bachmann S, Theilig F. Connexin 37 is localized in renal epithelia and responds to changes in dietary salt intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 35 publications
1
25
1
1
Order By: Relevance
“…These results suggest that -induced, BK-mediated K efflux has both P 2 -dependent and P 2 -independent components and -induced ATP release is dependent on K efflux. That K efflux is dependent on ATP efflux was revealed by application of carbenoxolone, an inhibitor of connexins and hemichannels (47). In C11, carbenoxolone inhibited 72% of the -induced K efflux and nearly all ATP release, suggesting dependence of K efflux on ATP extrusion via connexins.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that -induced, BK-mediated K efflux has both P 2 -dependent and P 2 -independent components and -induced ATP release is dependent on K efflux. That K efflux is dependent on ATP efflux was revealed by application of carbenoxolone, an inhibitor of connexins and hemichannels (47). In C11, carbenoxolone inhibited 72% of the -induced K efflux and nearly all ATP release, suggesting dependence of K efflux on ATP extrusion via connexins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cx37 expression was noticed in intraglomerular capillaries, while expression of Cx43 was only minor [12,14,25]. Furthermore, Panx3 presence has been seen in these cells [17].…”
Section: Glomerular Endotheliummentioning
confidence: 95%
“…The role of other epithelial Cxs in tubular function is still unknown. However, rats treated with low-salt diet showed a significant increase in Cx37 levels in renal cortex, which may indicate a functional role for this Cx species in renal tubules [25]. In addition, a recent study from Hanner and collaborators demonstrated a major role for Panx1-based channels in ATP release.…”
Section: Gap Junctions and Tubular Functionmentioning
confidence: 96%
See 1 more Smart Citation
“…The abundance of phosphorylated NHE3 was increased in proximal tubule brush-border membrane fractions in response to a high sodium intake, which may have contributed to its redistribution within the microvilli (72). A high salt intake has been shown to alter the expression and/or activity of a number of signaling molecules in the thick ascending limb, including endothelial nitric oxide synthetase, cytochrome P-450 epoxygenase, cyclooxygenase-2, AMP-activated protein kinase, and connexin 37 (20,36,39,61,63,73). Whether these or other signaling pathways may contribute to the adaptive increase in NHE3 activity and HCO 3 Ϫ absorption caused by high sodium intake in the MTAL remains to be determined.…”
Section: Of Hcomentioning
confidence: 99%